2017
DOI: 10.1159/000456714
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Gastrointestinal Cancer

Abstract: People living nowadays with HIV and AIDS may be treated effectively regarding virus replication and immunology. However, non-AIDS-defining cancer is of growing relevance due to high incidence and unfavorable outcome. The aim of this review is to summarize current knowledge on gastrointestinal (GI) carcinoma. Although literature on GI cancer is rare, an increased incidence of esophageal, gastric, pancreatic, hepatocellular, and colorectal carcinoma has been demonstrated. However, there are only few reports on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Human Immunodeficiency Virus (HIV) infection may increase the risk of ICC [62]. A U.S. case-control study (625 cases, 90,834 controls) found HIV to have an OR of 5.9 (95% CI 1.8-18.8) [63].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Human Immunodeficiency Virus (HIV) infection may increase the risk of ICC [62]. A U.S. case-control study (625 cases, 90,834 controls) found HIV to have an OR of 5.9 (95% CI 1.8-18.8) [63].…”
Section: Risk Factorsmentioning
confidence: 99%
“…This is another concern in older adults. About a third of HIV-positive persons are reported to die from cancer in their lifespan (Jensen et al 2017;Ehren et al 2014). HIV-infected patients demonstrate an increased risk of both HIV-related and non-HIV-related malignancies, especially for tumors of the breast, melanoma, pancreas, larynx, prostate, colorectum, and lung cancer.…”
Section: Malignancy In Hivmentioning
confidence: 99%
“…HIV-infected patients demonstrate an increased risk of both HIV-related and non-HIV-related malignancies, especially for tumors of the breast, melanoma, pancreas, larynx, prostate, colorectum, and lung cancer. There is an increase in adjusted cancer-specific mortality for the following GI malignancies: pancreas (hazard ratio (HR) 1.71), colorectum (HR 1.49), and liver (HR 1.1) (Jensen et al 2017;Gotti et al 2014;Coghill et al 2015).…”
Section: Malignancy In Hivmentioning
confidence: 99%
“…Several studies have reported cancer epidemiology and screening interventions in patients with HIV infection [45678]. However, gastric cancer data have been too limited to allow specific screening recommendations.…”
Section: Introductionmentioning
confidence: 99%